Teknik Pengobatan Tradisional Pada Masyarakat Melayu di Semendo Darat Ulu Kabupaten Muara Enim - Fitria Hayani Effendi; Nyimas Umi Kalsum; Aulia Desita; Hizbullah Hizbullah (Universitas Al Azhar Indonesia, 2023)
Malay people have a tendency to choose traditional medicine as an alternative in treating diseases. Treatment is a process of healing by using tools. The types of traditional medicine in Indonesia broadly consist of traditional medicine with medicinal herbs derived from nature, while traditional kebatinan medicine consists of traditional medicine on the basis of belief, religion, and on the basis of magnetic vibrations. Traditional medicine used by people in several regions in Indonesia is very diverse, including traditional medicine practiced by one of the Malay tribes in South Sumatra Province, Muara Enim Regency, namely the Semendo tribe. This research aims to complement existing references regarding traditional medicine, this research focuses on traditional medicine techniques in the Semendo tribe community, Muara Enim Regency. This descriptive qualitative research aims to explore the sources of knowledge, types and practices of traditional medicine in the Semendo tribe. The results showed that traditional medicine techniques in the Semendo tribe are carried out in 3 ways, namely, drinking, smearing or sticking using plants from nature, and internally. Traditional medicine in the Semendo tribe, Muara Enim Regency is still preserved to this day. This is due to the very high level of public trust in the efficacy of traditional medicine.Keywords - Malay, Nature, Prayer, Semendo, Traditional medicine.